Pengaruh Lingkungan Kerja, Fasilitas Dan Motivasi Kerja Terhadap Kinerja Pegawai Pada Pt. Bank Mandiri Persero Tbk Cabang Medan Balai Kota - Muchril Ardiansyah Putra (CERED Indonesia Institute, 2021)
Then it is defined descriptively, because to explain the data obtained and to answer the formula we will direct the results. From the research results indicate that motivation partially has a positive and significant effect on employee performance at PT. Bank Mandiri Persero Tbk Cabang Medan City Hall, facilities partially have a positive and significant influence on employee performance at PT. Bank Mandiri Persero Tbk Branch Medan City Hall, partially motivation has a positive and significant influence on employee performance at PT. Bank Mandiri Persero Tbk Cabang Medan City Hall, and work environment, facilities and motivation have a significant effect on employee performance at PT. Bank Mandiri Persero Tbk Medan City Hall Branch.